College student's academic help-seeking behavior: a systematic literature review - Li, Ruihua; Che Hassan, Norlizah; Saharuddin, Norzihani (Multidisciplinary Digital Publishing Institute, 2023)
Seeking academic help has a positive impact on students’ ability to handle challenges, leading to improved academic success. As the academic landscape becomes more competitive, the importance of students seeking and using academic support is widely recognized for enhancing their learning experience and achievements. The main objective of this study is to review the prior literature that has examined the academic support provided to college students, addressing the knowledge and methods required in an academic help-seeking process. Based on a systematic literature review, this study’s data were gathered from a review of 55 documents from the 11 years between 2012 and 2022. The literature was then individually analyzed using the ATLAS.ti 22 programs. The analysis shows five central themes: (1) Defining student help-seeking; (2) Academic help-seeking and academic performance; (3) Resources of academic help-seeking; (4) Factors of academic help-seeking; (5) Academic Help Seeking Online. This study also identifies potential new directions for future research that could be useful to school administrators in developing policies to assist students with help-seeking behavior, which could have significant implications for the theoretical development and practical guidance of student help-seeking behavior.